2014
DOI: 10.1093/poq/nfu027
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Test of the Effects of Survey Sponsorship on Internet and Mail Survey Response

Abstract: Survey researchers have typically assumed that university sponsorship consistently increases response rates and reduces nonresponse error across different populations, but they have not tested the effects of utilizing different university sponsors to collect data from the same population. In addition, scholars have not examined how these effects differ for mixed-mode (web and mail) or mail-only data collection. To explore these questions, we conducted an experiment in spring 2012 with an addressbased sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 17 publications
2
18
0
1
Order By: Relevance
“…Further, while the influence of a spouse/partner on work patterns emerged in the data from some respondents, future studies could explore this factor more deeply as it relates to sustaining patterns of intensive work. Research designs that consider these factors along with survey timing (Pennings, Irwin & Good, 2002 ), the sender of a questionnaire (M. L. Edwards, Dillman, & Smyth, 2014 ), and sponsor prominence (Boulianne, Klofstad & Basson, 2010 ), along with the use of incentives to participate in the research (Göritz, 2004 ), may be useful research strategies to deliver a more proportional sample in future studies, thus allowing more representative analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Further, while the influence of a spouse/partner on work patterns emerged in the data from some respondents, future studies could explore this factor more deeply as it relates to sustaining patterns of intensive work. Research designs that consider these factors along with survey timing (Pennings, Irwin & Good, 2002 ), the sender of a questionnaire (M. L. Edwards, Dillman, & Smyth, 2014 ), and sponsor prominence (Boulianne, Klofstad & Basson, 2010 ), along with the use of incentives to participate in the research (Göritz, 2004 ), may be useful research strategies to deliver a more proportional sample in future studies, thus allowing more representative analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the university sponsorship might have been more salient in the no cover image treatment because there were no images to distract from it. Easily identifiable and likely positively valued university sponsorship might have motivated participation (Edwards, Dillman, and Smyth 2014). Although we cannot empirically identify why the default cover design depressed response rates, the finding suggests that a mail survey's cover design can affect response rates if questionnaire designers somehow get the cover design "wrong.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, those who are less tolerant of homosexuality might be acting in ways consistent with findings from cognitive interview testing of same-sex couple categories for marital status questions: they view the LGB-inclusivity unfavorably, but will still respond to the survey (Ridolfo, Perez, and Miller 2011). It is also possible that the omnibus survey's topics or university sponsorship held more leverage for motivating participation than the LGB-inclusivity had at diminishing it among those who tend to be less tolerant of homosexuality (Edwards, Dillman, and Smyth 2014). For example, the university sponsorship may have overridden any negative perceptions of the LGB cover images.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative factors here are survey mode, sponsorship, the number of contacts, the reminder or the device used to participate in the survey, all of which could be explored to better understand survey participation as a holistic concept. Edwards et al (2014) have shown that survey sponsorship increases survey participation. Converse et al (2008) have provided evidence for differences in response rates according to the order of the survey modes in mixed-mode surveys.…”
Section: Summary and Discussionmentioning
confidence: 99%